Social‐economic theory and short‐term mate preferences: The effects of gender roles and socioeconomic status. (8th October 2015) - March, Evita; Grieve, Rachel
Abstract: Objective: Men's and women's mate preferences in long‐term relationships have been extensively considered in research. However, men's and women's short‐term mate preferences have not received nearly as much attention. In particular, theoretical origins of men's and women's short‐term mate preferences have received limited consideration in comparison to long‐term relationships. Specifically, although evolutionary origins of short‐term mate preferences have been discussed, elements of social‐economic theory (i.e., socioeconomic status (SES) and gender roles) have not yet been explored. The current study sought to address the gap in the literature concerning short‐term mate preferences and social‐economic theory. Method: Seven hundred eighty‐one participants were recruited to complete a questionnaire that included the mate budget paradigm. Results: For men, results showed significant independent effects of SES and gender roles on a short‐term mate's physical attractiveness scores, but no significant interaction. Results also showed no significant main effect of SES and gender roles on short‐term mate's social level scores, although there was a significant interaction between a masculine gender role and medium and high SES. For women, there were no independent or interactive effects of SES and gender roles on physical attractiveness and social level scores. Discussion: Results were interpreted in relation to both evolutionary and social‐economic theories, specifically discussing strategic pluralism and sexual strategies theories. Results of the study highlight the need for increased awareness of independent and interactional effects of social‐economic theory elements on men's and women's short‐term mate preferences, and further exploration of relationships outside the dichotomy of long and short term.